Conflicts in Organizations of Lithuania - Kulvinskienė, Violeta Raimonda; Stancikas, Edmundas Regimundas (Ekonomika, 2003)
Organizations engaged in different activities were investigated, i.e. manufacturing, trading and insurance. The number of respondents was 110, about 24 % were managers.The data of the investigation showed that negative approach towards conflicts is still very viable: quite many of employees (especially managers) are of the opinion that conflicts are the causes of low work efficiency, they provoke aggression, that is why it is better to avoid and ignore them. About 55% of conflicts between managers and subordinates occur because of the different point of view concerning the same problem or undervaluation of subordinates efforts. The employees of the insurance companies try to make a compromise (75,5%) with their customers or avoid (12,5%) the problems. The managers of the manufacturing and trading companies arc competition (36,3%) and avoidance (47,7%) of conflicts styled employees. but their behaviour is considered to be based on compromise and cooperation. The third party in conflict situations usually are the top managers. Employees indicated that about 34,3% of managers behave than to be intermediaries trying to help the conflict partners to come to a constructive decision. Usually they play to role of an arbiter, lessening the satisfaction of managing the conflict situations and extending the understanding of the conflict as the negative phenomenon. Dealing with conflict situations’ the managers in their own opinion. lack the knowledge of management, psychology and experience in managing the conflicts.